Molecular cytogenetic characterization of a new wheat-Thinopyrum intermedium homoeologous group-6 chromosome disomic substitution line with resistance to leaf rust and stripe rust - Zhang, Xiaojun; Li, Jianbo; Ge, Yudi; Guan, Haixia; Li, Guangrong; Zhang, Shuwei; Wang, Xiaolu; Li, Xin; Chang, Zhijian; Zhang, Peng; Jia, Juqing; Liu, Cheng (Frontiers in Plant Science, 2022)
Thinopyrum intermedium (JJJsJsStSt, 2n = 6x =42), a member of tertiary gene pool of hexaploid wheat (Triticum aestivum L., AABBDD, 2n = 6x = 42), provides several beneficial genes for wheat improvement. In this study, line CH51 was developed from the BC1F8 progeny of a partial wheat-Th. intermedium amphiploid TAI8335 (2n = 56) and wheat cultivar (cv.) Jintai 170. Somatic metaphase chromosome counting showed that CH51 had stable 42 chromosomes. Genomic in situ hybridization (GISH) analysis showed that CH51 had 40 wheat chromosomes and two Th. intermedium chromosomes involving translocation between Js- and St-genome chromosomes. Non-denaturing fluorescence in situ hybridization (ND-FISH) analysis revealed that CH51 lacked a pair of wheat chromosome 6B. Wheat 55K SNP array analysis verified that chromosome 6B had the maximum highest percentage of missing SNP loci in both CH51 and Chinese Spring (CS) nullisomic 6B-tetrasomic 6D (CS-N6BT6D) and had the maximum highest percentage of polymorphic SNP loci between CH51 and cv. Jintai 170. We identified that CH51 was a wheat-Th. intermedium T6StS.6JsL (6B) disomic substitution line. Disease resistance assessment showed that CH51 exhibited high levels of resistance to the prevalent Chinese prevalent leaf rust and stripe rust races in the field. Therefore, the newly developed line CH51 can be utilized as a potential germplasm in wheat disease resistance breeding.